Upaya Badan Pertanahan Nasional dalam Mencegah Sertifikat Ganda pada Program PTSL - Kurnia, Yuniva; Wisnaeni, Fifiana (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2025)
ABSTRACKThe PTSL program is a manifestation of the large amount of island in Indonesia that has not been certified. The purpose of this study is to analyze what efforts have been made by BPN in preventing the occurrence of multiple certificates in the PTSL program, as well as what factors have caused the occurrence of multiple certificates in BPN. The research uses a type of doctrinal research, namely research that focuses on the conception of law seen as a set of laws and regulations that are arranged systematically according to sequence with the characteristic of harmonization. The results of the study show that: 1) efforts made by BPN are in the form of efforts to implement regulations, efforts to socialize to the community, efforts to regress by increasing synergy with stakeholders. 2) the causative factor is the implementation of regulations that are not optimal and the public's ignorance of land registration procedures.Keywords: BPN; Double Certificate; PTSL.ABSTRAKProgram PTSL merupakan implementasi dari masalah besar tanah yang belum bersertifikat di Indonesia. Penelitian ini bertujuan untuk menganalisis langkah-langkah yang diambil oleh Badan Pertanahan Nasional (BPN) dalam mencegah terjadinya sertifikat ganda dalam program PTSL, serta faktor-faktor yang menyebabkan terjadinya sertifikat ganda di BPN. Penelitian ini menggunakan pendekatan doktrinal, yang meneliti konsep hukum sebagai serangkaian peraturan yang tersusun secara sistematis dengan harmonisasi yang khas. Hasil penelitian menunjukkan bahwa: 1) BPN melakukan upaya melalui penerapan regulasi, sosialisasi kepada masyarakat, dan sinergi dengan para pemangku kepentingan. 2) Faktor penyebabnya adalah pelaksanaan aturan yang kurang optimal dan kurangnya pemahaman masyarakat tentang prosedur pendaftaran tanah.Kata Kunci: BPN; Sertipikat Ganda; PTSL.